Nanoantidote for repression of acidosis pH promoting COVID‐19 infection. Issue 4 (1st May 2022) - Liu, Qidong; Ruan, Huitong; Sheng, Zhihao; Sun, Xiaoru; Li, Siguang; Cui, Wenguo; Li, Cheng
Abstract: Acidosis, such as respiratory acidosis and metabolic acidosis, can be induced by coronavirus disease 2019 (COVID‐19) infection and is associated with increased mortality in critically ill COVID‐19 patients. It remains unclear whether acidosis further promotes SARS‐CoV‐2 infection in patients, making virus removal difficult. For antacid therapy, sodium bicarbonate poses great risks caused by sodium overload, bicarbonate side effects, and hypocalcemia. Therefore, new antacid antidote is urgently needed. Our study showed that an acidosis‐related pH of 6.8 increases SARS‐CoV‐2 receptor angiotensin‐converting enzyme 2 (ACE2) expression on the cell membrane by regulating intracellular microfilament polymerization, promoting SARS‐CoV‐2 pseudovirus infection. Based on this, we synthesized polyglutamic acid‐PEG materials, used complexation of calcium ions and carboxyl groups to form the core, and adopted biomineralization methods to form a calcium carbonate nanoparticles (CaCO3 ‐NPs) nanoantidote to neutralize excess hydrogen ions (H + ), and restored the pH from 6.8 to approximately 7.4 (normal blood pH). CaCO3 ‐NPs effectively prevented the heightened SARS‐CoV‐2 infection efficiency due to pH 6.8. Our study reveals that acidosis‐related pH promotes SARS‐CoV‐2 infection, which suggests the existence of a positive feedback loop in which SARS‐CoV‐2 infection‐induced acidosis enhances SARS‐CoV‐2 infection. Therefore, antacid therapy for acidosis COVID‐19 patients is necessary. CaCO3 ‐NPs may become an effective antacid nanoantidote superior to sodium bicarbonate. Abstract : Acidosis‐related pH promotes SARS‐CoV‐2 pseudovirus infection by increasing cell membrane ACE2 expression. A CaCO3 ‐NPs antacid nanoantidote restored the normal blood related pH 7.4, attenuating the SARS‐CoV‐2 pseudovirus infection. This study suggests the existence of a positive feedback loop in which SARS‐CoV‐2 infection‐induced acidosis enhances further SARS‐CoV‐2 infection. CaCO3 ‐NPs nanoantidote may become an effective antacid.